Improving Student Learning Outcomes and Activities of the Implementation of Learning Model Student Teams Achievement Divisions / Meningkatkan Aktivitas dan Hasil Belajar Siswa Dengan Penerapan Model Pembelajaran Student Teams Achievement Divisions - Dita Martha Salecha (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2015)
This study aims to determine the implementation of the cooperative learning model STAD towards activities and learning outcome of Service Excellence. This research is categorized as a classroom action research using qualitative descriptive approach. The study subjects consisted of one class, which is X Marketing class of SMK PGRI 2 Malang. Yet, the research instrument is in a form of post-test. Furthermore, the data analysis for data activity is calculated by dividing the total score of each descriptor with descriptor which then multiplied by 100. Meanwhile, to calculate the average of the learning results, it is done by dividing the total score with the number of complete students.Results of data analysis showed that the implementation of cooperative learning model STAD can enhance learning activities on Service Excellence. In addition, the learning outcome of X grade students of Marketing also increased. Thus, it can be said that the implementation of the cooperative learning model STAD can enhance the activity and learning outcome for the X grade students of Marketing at SMK PGRI 2 Malang on Service Excellence. Abstrak: Penelitian ini bertujuan untuk mengetahui implementasi pembelajaran kooperatif model STAD terhadap aktivitas dan hasil belajar Pelayanan Prima. Penelitian ini termasuk jenis Penelitian Tindakan Kelas dengan menggunakan pendekatan deskriptif kualitatif. Subjek penelitian ini terdiri dari satu kelas X Pemasaran SMK PGRI 2 Malang. Instrumen penelitian berupa tes yang terdiri dari post-test. Analisis data untuk aktivitas data dihitung dengan membagi skor tiap deskriptor dengan total deskriptor kemudian di kali 100. Sedangkan untuk menghitung rata-rata dari hasil belajar dengan membagi jumlah nilai keseluruhan dengan jumlah siswa.Hasil analisis data menunjukkan bahwa implementasi pembelajaran kooperatif model STAD dapat meningkatkan aktivitas belajar Pelayanan Prima. Selain itu hasil belajar siswa kelas X Pemasaran juga mengalami peningkatan. Dengan demikian dapat dikemukakan bahwa implementasi pembelajaran kooperatif model STAD dapat meningkatkan aktivitas dan hasil belajar Pelayanan Prima pada kelas X Pemasaran di SMK PGRI 2 Malang.